The Prototype of Pest Repellent System and Insect Light Trap using Solar Energy for Small Agriculture - Md Khairi, Muhammad Afiq Fiikri; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, agriculture is a source of income for Malaysians from mass cultivation to courtyards. This study is to find an alternative for farmer from using pesticides that can be harmful to the health of consumers. This study also demonstrates the level of stimulation animals towards sound through certain frequencies and how to trap insects with light at night. Thus, the project was tackled farmer from using chemical on plants by developing of prototype pest repellent and insect light trap using solar energy as alternative power supply. For the pest repellent development, Passive Infra-Red (PIR) sensor as a main function to detect a motion before Arduino UNO read and give the frequency value specified by user using potentiometer. The ESP8266 board also through used to know the motion between system devices to the Blynk platform. Blynk is a Platform used to achieve the Internet of Thing (IoT) for this project. LCD display also will display the signal from PIR sensor whether pest detected or pest not detected. For insect light trap development, relay is the main component to turn on the light. When solar panel not generate energy, the relay will trigger to turn up the light. One container with half of water will trap the insect when it’s come near the light.